2017
DOI: 10.7567/jjap.57.02bc05
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of low temperature Cu/In bonding for fine-pitch interconnects in three-dimensional integration

Abstract: This study presents the results for Cu/In bonding based on the solid–liquid interdiffusion (SLID) principle for fine-pitch interconnects in three-dimensional integration. The microbumps were fabricated on Si wafers (55 µm pitch, 25 µm top bump diameter, 35 µm bottom bump diameter). In was electroplated directly on Cu only on the top die microbumps. Two different In thicknesses were manufactured (3 and 5 µm). The interconnects were successfully fabricated at a bonding temperature of 170 °C. High temperature sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Over recent years, pure indium has been successfully employed as a low-temperature soldering material by Panchenko et al, and fine-pitch Cu–In bonding based on the SLID process was carried out at a peak temperature of 170 °C for 2 min [ 5 , 6 , 7 , 8 ]. In their research, the Cu/In joints revealed remarkable shear strengths, ranging from 45 to 120 MPa [ 7 ], which were comparable with the strengths of Cu/Sn interconnects [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over recent years, pure indium has been successfully employed as a low-temperature soldering material by Panchenko et al, and fine-pitch Cu–In bonding based on the SLID process was carried out at a peak temperature of 170 °C for 2 min [ 5 , 6 , 7 , 8 ]. In their research, the Cu/In joints revealed remarkable shear strengths, ranging from 45 to 120 MPa [ 7 ], which were comparable with the strengths of Cu/Sn interconnects [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the solid-state interfacial reactions between In and Cu, a layer of CuIn 2 was discovered at the interface of sequentially evaporated Cu/In thin films [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ] and as-electroplated Cu/In films [ 6 , 7 , 23 ] at room temperature. Although the CuIn 2 phase was not included in the latest equilibrium Cu–In phase diagram as shown in Figure 1 [ 24 ], its formation in bulk Cu–In [ 25 , 26 ] and Cu–In–S [ 25 , 27 ] alloys after quenching indicated that it is a stable phase at room temperature and is likely formed through the peritectoid reaction between Cu 11 In 9 and In [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to investigate the low-temperature Cu-In bonding [2], [10]- [15]. At room temperature, the stable phases in Cu-In binary system are Cu, , and In.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous experimental results and the Cu-In binary phase diagram, various IMCs (Cu7In3 (δ), Cu2In (η), Cu11In9, CuIn2, Cu16In9, and CuIn ) can appear during bonding [2], [3], [10]- [13], [16], [17], and phase transformation can occur during aging. Voids with different sizes appear after aging due to the volume shrinkage between different phases [15]. According to Roy [18] and Chen [19], the CuIn intermetallic compound forms even at room temperature, and it can be formed immediately after In deposition on Cu.…”
Section: Introductionmentioning
confidence: 99%
“…For Cu/Sn TLP bonding (Chen and Duh, 2017), studied the microstructures evolution of Cu/Sn-3.5Ag/Cu-xZn using TLP bonding; it can be found that the addition of 15% Zn into Cu substrate can availably maintain the IMCs multi-orientation structure and restrain the growth of Cu 3 Sn layer during aging. For Cu/In bonding, Cu 11 In 9 and Cu 2 In, two IMCs, layers can be observed simultaneously during isothermal storage (Panchenko et al, 2018). In this article, we have studied the formation of Ni 3 Sn 4 IMC with different bonding time using TLP bonding; moreover, the finite element code was utilized to calculate the stress-strain distribution to predict the effect of IMC thickness on the fatigue life of solder joints.…”
Section: Introductionmentioning
confidence: 99%